Current and future directions in infant research: How can multiple measures help us learn more? - Porru, Annamaria; Bastianello, Tamara; Addabbo, Margaret; Calignano, Giulia; Decarli, Gisella; Gemignani, Jessica (Frontiers in Developmental Psychology, 2026)
The complexity of early infancy poses relevant challenges for researchers aiming to understand developmental processes. While infants are active learners, their communication modalities remain limited and rudimentary during the first 2 years of life. Consequently, it is particularly challenging to explore their cognitive abilities and track their socio-emotional developmental trajectories. The standard model in the field has been to consider one measurement method as sufficient for detecting and quantifying developmental phenomena. However, only a multiple measures design permits verification of each measure's alignment with the underlying construct and yields less equivocal functional interpretations supported by convergent empirical signals. In this perspective paper, we emphasize the importance of adopting a multiple measures approach and provide practical recommendations and suggestions, including strategies for applying these methods. Specifically, we illustrate how integrating these methods can enable researchers to draw meaningful conclusions in infant research. Finally, we argue that the complexity arising from the critical selection of a multiple measures approach should be viewed as a unique opportunity to formulate robust developmental theories capable of predicting outcomes across different domains, rather than a limitation. However, multiple measures research is not free of challenges. Recognizing the strengths and limitations of integrating multiple measures is the first step toward developing an integrative approach that preserves ecological validity while producing robust and meaningful results. In conclusion, this paper aims to encourage developmental psychology researchers to critically embrace multiple measures research, despite the additional effort and time it may require.